2000
DOI: 10.1073/pnas.100113197
|View full text |Cite
|
Sign up to set email alerts
|

Automated parallel DNA sequencing on multiple channel microchips

Abstract: We report automated DNA sequencing in 16-channel microchips. A microchip prefilled with sieving matrix is aligned on a heating plate affixed to a movable platform. Samples are loaded into sample reservoirs by using an eight-tip pipetting device, and the chip is docked with an array of electrodes in the focal plane of a four-color scanning detection system. Under computer control, high voltage is applied to the appropriate reservoirs in a programmed sequence that injects and separates the DNA samples. An integr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
74
0
2

Year Published

2000
2000
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(76 citation statements)
references
References 41 publications
0
74
0
2
Order By: Relevance
“…CE/MS analysis of a four-protein mixture using a PAA-coated microchip coupled to an ESI-MS. The sample concentration was 2 mM of each protein in 5 mM NH 4 Ac/ HAc (pH 4.4). Reprinted from [74], with permission.…”
Section: Pvpmentioning
confidence: 99%
See 1 more Smart Citation
“…CE/MS analysis of a four-protein mixture using a PAA-coated microchip coupled to an ESI-MS. The sample concentration was 2 mM of each protein in 5 mM NH 4 Ac/ HAc (pH 4.4). Reprinted from [74], with permission.…”
Section: Pvpmentioning
confidence: 99%
“…Microfluidic devices have been applied for electrophoretic separations for a variety of biochemical and chemical analysis [1][2][3][4][5][6][7]. Latest developments in microchip electrophoresis (MCE) have been summarized in recent reviews [8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Microchip electrophoresis (MCE), based on the separation principle of CE, has been widely used in the analysis of chemical and biogenic compounds because of its high performance, high speed, compactness, and low consumption of solvents and samples. [14][15][16][17][18][19][20] These characteristics of MCE are very suitable for the development of a high-throughput chiral-analysis system.…”
Section: Introductionmentioning
confidence: 99%
“…Since then, many other papers reporting four-color DNA sequencing in glass and plastic chips have been published (10,(20)(21)(22)(23)(24), with Salas-Solano et al (19) achieving 580 base reads in 18 min and 640 base reads in 30 min in single-channel fused silica glass chips. In these studies, read lengths are reported either with a certain accuracy when obtained read lengths are compared with the known DNA sequence (usually using a cutoff accuracy of 98.5%) or by using a quality assessment program called phred, which assigns a quality score based on peak shapes, where a called base with a phred score of 20 (Q20) has a 99% probability of being correct.…”
mentioning
confidence: 99%
“…In these studies, read lengths are reported either with a certain accuracy when obtained read lengths are compared with the known DNA sequence (usually using a cutoff accuracy of 98.5%) or by using a quality assessment program called phred, which assigns a quality score based on peak shapes, where a called base with a phred score of 20 (Q20) has a 99% probability of being correct. To demonstrate the potential for increased throughput of microfluidic sequencing devices, Liu et al (20) Here, we report a microfluidic chip-based system that provides ultrafast DNA sequencing, providing read lengths up to 600 bases in 6.5 min using a high-performance polymer system comprised of both a separation matrix and a physically adsorbed microchannel wall coating. Previously published microchip sequencing results have exclusively used linear polyacrylamide (LPA) as the sequencing matrix as well as a covalently bonded LPA coating for the channel walls, with analysis times in these systems ranging from 15 to 35 min.…”
mentioning
confidence: 99%